Kosovo Jobs Diagnostic - Cojocaru, Alexandru (World Bank, Washington, DC, 2017)
Kosovo's economy experienced strong growth over the past decade. Has growth translated into robust job creation? Do those in the bottom forty percent of the population have access to employment opportunities that can translate into sustainable shared prosperity? This report seeks to provide an integrated analysis of the demand-side and supply-side constraints to job creation and employment; and highlighting salient issues like informality and skill mismatches. Bringing together evidence from a number of data sources, including surveys of household budgets and labor force, as well as firm-level panel data and a specialized survey capturing the employers' assessments of demand and supply of skills in Kosovo, the report tries to provide evidence to argue that reforms aimed at adopting the right set of rules, and developing the right set of skills, to promote job creation, will be vital to reduce inactivity and youth disenfranchisement, and to productively employ the demographic dividend.